Modeling gradual diffusion changes in radiation belt electron phase space density for the March 2013 Van Allen Probes case study. Issue 10 (28th October 2014) - Li, Zhao; Hudson, Mary; Jaynes, Allison; Boyd, Alexander; Malaspina, David; Thaller, Scott; Wygant, John; Henderson, Michael
Abstract March 2013 provided the first equinoctial period when all of the instruments on the Van Allen Probes spacecraft were fully operational. This interval was characterized by disturbances of outer zone electrons with two time scales of variation, diffusive and rapid dropout and restoration. A radial diffusion model was applied to the monthlong interval to confirm that electron phase space density is well described by radial diffusion for the whole month at low first invariant ≤ 400 MeV/G but peaks in phase space density observed by the Energetic Particle, Composition, and Thermal Plasma (ECT) instrument suite at higher first invariant are not reproduced by radial transport from a source at higher L. The model does well for much of the monthlong interval, capturing three of four enhancements in phase space density which emerge from the outer boundary, while the strong enhancement following dropout on 17–18 March requires local acceleration at higher first invariant (M=1000 MeV/G versus 200 MeV/G) not included in our model. We have incorporated phase space density from ECT measurement at the outer boundary and plasmapause determination from the Electric Field and Waves (EFW) instrument to separate hiss and chorus loss models.